Urban Meyer Needs an Image Repair Coach. Issue 2 (2nd April 2020) - Hanna, Chris; Morton, James T.
Abstract: Ohio State University football coach Urban Meyer became the subject of controversy when it was reported that one of his assistant coaches, Zach Smith, allegedly abused his spouse. Scrutiny followed the Smith reports as the media and public tried to understand Meyer's interactions with Smith, knowledge of Smith's conduct, proper reporting of that conduct, and handling of public relations prior to the 2018 college football season. Image repair theory (also known as image restoration theory) is utilized in this case study to assess Meyer's public relations tactics in a time of crisis from July 24, 2018 to Sept. 22, 2018. This longitudinal approach specifically focused on a coach's image repair quotes provides a unique contribution to the literature. Meyer used four of the five major image repair strategies noted by Benoit, more heavily leaning on reducing offensiveness of the event and mortification with the passing of time.